Empirical legitimacy as core of comparative democracy research - Pickel, Gert; Pickel, Susanne (Frontiers in Political Science, 2024)
Legitimacy is a central resource for all political systems. This include democracies as autocracies. For democracies, you need the acceptance of the normative concept of democracy by the citizens. Simply put, this norm requires an empirical legitimacy. The empirical legitimacy focus on different understandings of democracy. Mostly the aspect of individual freedom is dominant. Empirical analyses show this idea do not only work for Europe. The article first shows what empirical legitimacy means conceptually and then analyzes this existence of legitimacy in a comparative perspective. It is the erosion of legitimacy that can lead a political regime to collapse. Current survey data from political culture research show not only differences in the legitimacy of democratic and autocratic regimes, but also an increase in the importance of different understandings of democracy. Some of these are no longer democratic.